A comparison of career success between graduates of vocational and academic tertiary education - Backes-Gellner, Uschi [Verfasser]; Geel, Regula [Verfasser] (My University, 2014)
"This paper analyses whether tertiary education of different types, i.e., academic or vocational tertiary education, leads to more or less favourable labour market outcomes. We study the problem for Switzerland, where more than two thirds of the workforce gain vocational secondary degrees and a substantial number go on to a vocational tertiary degree but only a small share gain an academic tertiary degree. As outcome variables, we examine the risk of being unemployed, monthly earnings, and variation in earnings (reflecting financial risk). We study these outcomes at career entry and later stages. Our empirical results reveal that the type of tertiary education has various effects on these outcomes. At career entry, we observe equal unemployment risk but higher average wages and lower financial risk for vocational graduates. At later career stages, we find that these higher average wages disappear and risk of unemployment becomes lower for vocational graduates. Thus, by differentiating the tertiary system into vocational and academic institutions graduates face a variety of valuable options allowing them to self-select into an educational type that best matches their individual preferences." (Author's abstract, BIBB-Doku)
Vorab-Veröffentlichung als Leading House Working Paper No. 52 (January 2011) u.d.T.: "Career entry and success after tertiary vocational education"
Keywords: G 1.3.3.1 Qualifikationsverwertung; P 2.3 Auszubildende; P 2.6 Hochschulabsolventen; I 2.2.1 Westeuropa; Höhere Berufsbildung; Ausbildungsabsolvent; Hochschulabsolvent; Bildungsertrag; Arbeitsmarktchance; Lohnhöhe; Schweiz